How does self-compassion help people adjust to chronic skin conditions? A template analysis study - Clarke, Elaine N.; Norman, Paul; Thompson, Andrew R. (Frontiers in Medicine, 2022)
Objectives: Skin conditions can greatly impact people’s lives, but greater understanding of the processes involved in positive adjustment is required. Self-compassion has strong links to wellbeing and adaptive functioning and therefore may play an important role in adjustment to skin conditions. Design: Template analysis was used to explore how self-compassion operates in people living with skin conditions, with reference to existing theories of self-compassion. Methods: Semi-structured interviews were conducted with highly self-compassionate people with chronic skin conditions (N = 10). Theoretical models of self-compassion were used in the development of the initial template and interview schedule. Participants were purposively selected on the basis of having high scores on a measure of self-compassion. Results: Participants reported a variety of ongoing skin-related difficulties and their ways of managing these. Sensitivity to distress and care for wellbeing were identified as foundation themes: necessary components of a compassionate response to distress. Eleven types of difficulty-management strategies built upon these foundation themes: empathy, non-judgement, distress tolerance, self-kindness, mindful attention, perspective-taking, self-talk, self-care, using social support, concealment, and idiosyncratic coping strategies. Conclusions: Components of self-compassion helped people adjust to chronic skin conditions in a wide variety of ways, indicating that psychological adjustment is not a simple, linear process.Sometimes compassionate responses occurred automatically and sometimes with deliberate effort. Further research on compassion-based interventions for people with skin conditions is warranted.